Краевая задача для смешанного уравнения третьего порядка нараболо-гиперболического типа - Елеев, В.А. (Український математичний журнал, 1995)
The unique solvability of a certain boundary-value problem is proved for a mixed parabolic-hyperbolic type equation of the third order.